2000
DOI: 10.1021/ac000122+
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Optimization of a Real-Time, Parallel, Label-Free, Polypyrrole-Based DNA Sensor by Surface Plasmon Resonance Imaging

Abstract: We describe in this paper a methodology to quantify multispot parallel DNA hybridizations and denaturations on gold surfaces by using, on one hand, a polypyrrole-based surface functionalization based on an electrospotting process and, on the other hand, surface plasmon resonance imaging allowing real-time measurements on several DNA spots at a time. Two characterization steps were performed in order to optimize the immobilization of oligonucleotide probes and, thus, to increase the signal-to-noise ratio of mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
110
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 27 publications
1
110
0
Order By: Relevance
“…Surface plasmon resonance (SPR) imaging is a label-free, surface-sensitive spectroscopic technique that can be used to detect the binding of DNA, RNA, and proteins onto arrays of probe biomolecules covalently attached to chemically modified gold surfaces (Rich and Myszka, 2000). Our previous work focused on the creation and characterization of robust surface chemistries for the attachment of various biomolecules onto chemically modified gold surfaces with a novel methodology based on polypyrrole-based surface functionalization (Guedon et al, 2000). We also showed that multispot parallel DNA hybridization and denaturation could also be detected (Livache et al, 2003), unlike the commercially available instruments that are limited to four channel detection.…”
Section: Published Online 7 June 2004mentioning
confidence: 99%
See 2 more Smart Citations
“…Surface plasmon resonance (SPR) imaging is a label-free, surface-sensitive spectroscopic technique that can be used to detect the binding of DNA, RNA, and proteins onto arrays of probe biomolecules covalently attached to chemically modified gold surfaces (Rich and Myszka, 2000). Our previous work focused on the creation and characterization of robust surface chemistries for the attachment of various biomolecules onto chemically modified gold surfaces with a novel methodology based on polypyrrole-based surface functionalization (Guedon et al, 2000). We also showed that multispot parallel DNA hybridization and denaturation could also be detected (Livache et al, 2003), unlike the commercially available instruments that are limited to four channel detection.…”
Section: Published Online 7 June 2004mentioning
confidence: 99%
“…In step 1, the gold-coated prism is functionalized at different specific locations in the form of circular spots. On each spot, the specific single-strand zip-code oligonucleotide linked to a pyrrole residue (the probe) is electropolymerized on the gold surface by the methods described by Guedon et al (2000) leading to covalent binding on the chips. Some spots were created with free pyrrole used as negative control.…”
Section: Published Online 7 June 2004mentioning
confidence: 99%
See 1 more Smart Citation
“…Guedon et al, [20], reported a DNA hybridization sensor based on ppy-ODN matrix coupled with SPR imaging. They prepared SPR chip by electrospotting pyrrole and pyrrole linked to an oligonucleotide (ODN).…”
Section: Application Of Spr In Conducting Polymersmentioning
confidence: 99%
“…SPRI detects the specific binding of unlabeled biomolecules to arrayed capture molecules attached to a modified gold thin film by measuring changes in the local index of refraction upon adsorption (11). It has been proven to be a valuable tool for investigating molecular interactions without the use of any fluorescent or radiochemical labels (4,(6)(7)(8). Use of the SPR principle can be further expanded to the detection of microbial cells with immobilized antibodies or protein ligands on an SPR sensor chip (9,12).…”
mentioning
confidence: 99%